Electronic surveillance in the couple: The role of self-efficacy and commitment. (January 2021) - Ruggieri, Stefano; Bonfanti, Rubinia C.; Passanisi, Alessia; Pace, Ugo; Schimmenti, Adriano
Abstract: Researchers have shown a significant effect of using social networking sites (SNSs) on romantic relationships. Surveillance is one of the motives for social network use. Social networking surveillance is related to controlling a romantic partner's online behaviours. The purpose of the study was to search for antecedents of electronic surveillance (Study 1) and to examine their role in behaviours related to electronic surveillance among romantic couples (Study 2). Following the uses and gratification theory and technology acceptance model of using SNSs, antecedents of electronic surveillance in adult Facebook users were examined. In Study 1, the relationship between electronic surveillance and intimacy, commitment, marital satisfaction, interpersonal interaction, self-efficacy on SNSs, perceived usefulness, and perceived ease of use were tested in a group of 360 adults. Commitment and self-efficacy on SNSs were the best predictors of surveillance. In Study 2, an actor–partner interdependence model was used to test whether self-efficacy on SNSs predicted surveillance behaviours in 122 couples. Findings showed that electronic surveillance is a feature of a couple and not exclusively of the individual and suggest that self-efficacy on SNSs has a relevant role in predicting electronic surveillance. Highlights: Online surveillance in the couple also occurs in social networking sites (SNSs). Online surveillance is a feature of a couple and not of an individual member. Predictors of online surveillance were examined across two studies. Intimacy, commitment, and SNSs ease of use, usefulness and self-efficacy predicted online surveillance. APIM analyses showed that SNSs self-efficacy is a key variable for understanding online surveillance.